Program Edukasi Smart Home sebagai Upaya Peningkatan Literasi Teknologi pada Masyarakat Sukodono Sidoarjo - Sudarso Sudarso; Yayu Sriwahyuni; Muh. Saul Bayustira (Jurnal Kabar Masyarakat, 2026)
This Community Service activity aims to increase community technology literacy through Internet of Things (IoT)-based Smart Home education in Sukodono, Sidoarjo Regency. The implementation method includes socialization, training, demonstration, and evaluation using pre-test and post-test. The results showed a significant increase in participants' understanding, which was reflected in the increase in the average score from 58.5 to 81.2, as well as an increase in the percentage of participants with a score of ≥70 from 35% to 85%. In addition, participants gave a positive response and showed interest in the application of Smart Home technology in daily life. The demonstration-based educational approach has proven to be effective in strengthening people's technological literacy, as it is able to provide a hands-on experience that is easier to understand and apply. These findings confirm that real practice-based education can be a relevant strategy to introduce digital technology to the wider community. However, more applicable follow-up activities are needed to support the implementation of technology independently and sustainably, so that people not only understand the basic concepts, but also are able to integrate Smart Home technology in their daily activities productively and sustainably.